Enhancing production, value addition and marketing of indigenous vegetables, French beans and mushrooms among small holder farmers in Kenya. - Andika, Darius O. (Implemented in collaboration with four (4) local universities National Museums of Kenya, KIRDI and E.A. Nutraceuticals., 2014)
The project aims at implementing a research in vegetable value addition chain
A RIO Research Project